GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SD N JARAKAN KABUPATEN BANTULTAHUN AJARAN 2016/2017 - Dyah Hediana Windasari (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpuso of research is to determine : (1) The style of principal leadership in improving the professional competence of any that have been formed on the teachers; (2) the professional competence of any that have been formed on the teacher; (3) the principal obstacles and ways to improve the professional competence of teachers. This study a descriptivestudy with qualitative apporoach. Data collection techniques using observation, interviews, and documentation. Data analysis technique performed with data collection, data reduction, presenting data, and conclusions. The results showed that (1) the principal’s leadership style used improving the professional competence of teachers is the style of executive leadership, development, democratic, organizer and administrator; (2) professional competence that has been formed by the teacher is capable of mastering the subject matter in accordance with the field of study that teaches, is able to apply the methodology and learning strategies, capable of designing and utilizing various media and learning resources, is able to carry out the evalution of learning, capable of develop programs of learning, and able to carry out elements of support; (3) barriers experienced principals are the facilities, the age factor and bustle head teacher of the school. How did the head of the school in improving the professional competence of teachers is to give more credence to the teachers and training of teachers, PLPG, PPG, and teacher certification.